Violências vivenciadas por homens trans na educação superior: Bullying ou transfobia? - Santos, Samuel Oliveira (2024)
This Master's research, which was supported by the Coordination for the Improvement of Higher Education Personnel (CAPES), is part of the "Knowledge and Educational Practices" Research Line of the Postgraduate Program in Education at the Federal University of Uberlândia. The work is part of the discussions developed in the GPESP - Education, Sexualities and Perfomativities Research Group, and its theme is transphobic bullying at the intersection with Higher Education. The aim was to map the experiences of bullying experienced by transgender men during their initial training in undergraduate courses. This was a qualitative study with the participation of seven trans men, with an average age of 19 and 32 and from different municipalities and higher education backgrounds. The questionnaire and semi-structured interview were the tools used to generate the data. The results show that the transition process from basic to higher education is implicated by the transition process. In higher education spaces, the bathroom is an architecture of terror and the demarcation of differences. The social name and proper treatment were also questioned as challenging factors for the professionalization process. However, protective factors such as friendship, education professionals, family and health professionals were cited as possibilities that produce resistance.